Expectations of Chinese Immigrant Parents for Their Children’s Education: The Interplay of Chinese Tradition and the Canadian Context - Li, Jun (Canadian Journal of Education/Revue canadienne de l'éducation, 2001)
In this study, I used qualitative interviews to explore the expectations of the parents in seven Chinese families who had recently immigrated to Canada. These parents grounded their expectations for their children in Chinese tradition, their deeply rooted cultural heritage. Their personal life experiences and acculturative attitudes also shaped their expectations. The parents’ understanding of Canadian society and their perception that visible minorities are disadvantaged prompted them to form a minority ideology and also to advise their children to pursue science-related careers. The expectations of these parents were situationally motivated in different ways to conform to the Canadian socio- cultural context À l’aide d’interviews qualitatives, l’auteure a étudié les attentes des sept familles chinoises récemment arrivées au Canada. Les attentes de ces parents s’enracinent dans la tradition chinoise. Leurs expériences personnelles et leurs attitudes acculturatives façonnent également leurs attentes. Leur compréhension de la société canadienne et leur sentiment que les minorités visibles sont désavantagées les incitent à former une idéologie de la minorité et à conseiller à leurs enfants de viser une carrière dans les sciences. Les attentes de ces parents sont à divers égards motivées par une volonté de se conformer au contexte socioculturel canadien.